Aloe sterol supplementation improves skin elasticity in Japanese men with sunlight-exposed skin: a 12-week double-blind, randomized controlled trial [Corrigendum] - Tanaka M; Yamamoto Y; Misawa E; Nabeshima K; Saito M; Yamauchi K; Abe F; Furukawa F (Dove Medical Press, 2016)
Tanaka M, Yamamoto Y, Misawa E, et al. Clin Cosmet Investig Dermatol. 2016;9:435–442.On page 438, Figure 1, the y-axis title should have read “ΔR2 (%)” instead of “ΔR5 (%)”.On page 439, Figure 2, the y-axis title should have read “ΔR5 (%)” instead of “ΔR7 (%)”.Read the original article here.